Long-term survival of upper tract urothelial carcinoma patients in a tertiary care hospital - Nuwatkrisin, Kanrapee; Itsaranujareankul, Takarn; Panumatrassamee, Kamol; Sowanthip, Dutsadee; Opanuraks, Julin; Ratchanon, Supoj; Santingamkun, Apirak; Usawachintachit, Manint (Insight Urology, 2022)
Objective: Upper urinary tract urothelial carcinoma (UTUC) is an uncommon but rapidly progressive disease associated with a high mortality rate. Despite the advancement in surgical and medical treatment during the last decade, long-term clinical data pertinent to UTUC are still limited in Thailand. The objectives of this study were to identify the long-term survival rate and factors affecting the survival of UTUC patients. Materials and Methods: We reviewed medical records of UTUC patients treated at King Chulalongkorn Memorial Hospital from 2004 to 2019. We calculated 5-year survival rate using the Kaplan-Meier method and investigated its correlation with various clinicopathological factors through the Cox hazard regression model. Results: One hundred and twenty-seven UTUC patients were included in this study. There was a slight predominance of females (55.1%), and the mean age at diagnosis was 68.2 years. The majority of patients were TNM stage I (43.3%) followed by stage III (26.9%). The 5-year overall and cancer-specific survival rates were 62.2% and 75.6%, respectively. Based on univariable analysis, TNM stage, pathological T stage, pathological N stage, and lymph node dissection status were associated with the overall survival and cancer-specific survival. However, none of these factors remained statistically significant in the multivariate analysis. Conclusion: The 5-year overall survival rate of UTUC patients was 62.2%. TNM stage, pathological T stage, pathological N stage, and lymph node dissection status were associated with the overall survival. A further study with a higher population number is warranted to add weight to these findings and investigate their potential clinical use further.